Technology and trend management at the interface of technology push and market pull - Maier, Maximilian A.; Hofmann, Maximilian; Brem, Alexander (International Journal of Technology Management, 2016)
Technology push and market pull innovation strategies are playing an important role for the effective management of ideas, technologies, and trends. The coexistence of these two approaches led to many debates and the focus switched several times from putting more effort into technology push aspects to fostering market pull approaches in the last decades. Still, there is no in-depth exploration of the interface of technology push and market pull and only few conceptual models are dealing with the connection between technology push and market pull in particular. Therefore, this study puts an exploratory focus on the innovation management processes of a global outdoor manufacturer with a special emphasis on the interface between technology push and market pull. From the case findings and our literature we conceptualise a non-linear innovation model that systematically integrates market pull and technology push activities. The model was tested for its practical applicability by reflecting it against the case company's organisational capabilities. Further research implications are discussed as well as implications for the management of the innovation process in practice, which highlights especially the importance of an innovation competence tea